2015
DOI: 10.3109/09638237.2015.1057330
|View full text |Cite
|
Sign up to set email alerts
|

Poly-victimization and mental health of street children in Lahore city

Abstract: The most common type of victimization was conventional crime which negatively predicts mental health of street children. The results have important implications for the policy makers to develop improved services for this vulnerable group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…A total score can be created as the sum of these 34 questions. Since the introduction of the JVQ, it has been used in diverse settings, including in Finland [ 26 ], Spain [ 27 ], China [ 28 , 29 ], Pakistan [ 30 ] and Vietnam [ 31 ]. There have, however, been variations among studies in terms of the criteria used for determination of poly-victimisation.…”
Section: Introductionmentioning
confidence: 99%
“…A total score can be created as the sum of these 34 questions. Since the introduction of the JVQ, it has been used in diverse settings, including in Finland [ 26 ], Spain [ 27 ], China [ 28 , 29 ], Pakistan [ 30 ] and Vietnam [ 31 ]. There have, however, been variations among studies in terms of the criteria used for determination of poly-victimisation.…”
Section: Introductionmentioning
confidence: 99%
“…This dose–response relationship has also been confirmed in Burundian children with experiences of physical violence within their families and on the streets (Crombach & Elbert, 2014). In line with these results, two additional studies linked exposure to violence on the streets and poly‐victimization to mental health issues and psychological distress (Bashir & Dasti, 2015; Shein‐Szydlo et al, 2016). Most recently, Derivois et al (2017) confirmed the relationship between physical and psychological abuse on the streets and PTSD symptoms in children.…”
Section: Introductionmentioning
confidence: 62%
“…The questionnaire has good internal consistency (α = 0.80) and has been administered in China ( 71 ), Israel ( 72 ), Pakistan ( 73 ), Portugal ( 74 ), South Africa ( 75 ), Spain ( 76 ), and the United Kingdom ( 77 ), and has recently been adapted for use in a national study in Australia ( 70 ). The measure also demonstrates adequate test–retest reliability, with 200 of the respondents being re-contacted and re-administered the JVQ within 3–4 weeks of its original administration.…”
Section: Resultsmentioning
confidence: 99%
“…When considering the appropriateness of measures for gaining global estimates of childhood exposure to DVA, the researchers considered three main areas: firstly, which measure had been most commonly applied within LMICs, second, which was most acceptable according to the indicators covered in COSMIN PROMs, and finally, which measure covered aspects of exposure to DVA the closest, based on our current understanding. Three of the measures have been applied in LMICs—the CEDV, which has been implemented in Brazil ( 50 ), India ( 51 ), Iran ( 52 ), Iraqi-Kurdistan ( 53 ), Pakistan ( 54 ), and South Africa ( 55 ), the JVQ, which has been applied in China ( 71 ), Pakistan ( 73 ) and South Africa ( 75 ), and the CPIC, which has been applied in China ( 64–66 ), and Pakistan ( 67 ). Based on this information, it could be assumed that the CEDV is the most appropriate measure for assessing childhood exposure to DVA within LMICs, although it is still sparsely implemented.…”
Section: Discussionmentioning
confidence: 99%